Relationship Between Food Acceptability and The Amount of Leftover Food Among Patients in The Rehabilitation Room of Drug Dependence Hospital of Jakarta - Eka Puspitasari; Tri Ardianti Khasanah; Adhila Fayasari (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Acceptability of food is influenced by many related factors such as individual factor, food factor and environmental factor. The success of a food administration is often associated with the presence of leftover food consumed by the patient. Leftover food is also an indicator of the success of nutrition services in hospitals. This study aims to determine the relationship between food acceptability and the amount of leftover food among patients in the rehabilitation room of Drug Dependence Hospital of Jakarta. This was a descriptive study with a cross sectional approach. The study samples were selected using purposive sampling technique as many as 33 respondents. The results of bivariate analysis showed that there was a relationship between the leftover food and food temperature (p 0.017), the food serving time (p 0.006), and the suitability of cutlery used (p 0.009) with food acceptability. It can be concluded that there was a relationship between food acceptability and leftover food among patients in the rehabilitation room of Drug Dependence Hospital of Jakarta. It is recommended to conduct further study with a larger number of samples and involve other variables to find out which variables are related to food acceptability and food lefovers.